Frontiers in páramo water resources research: A multidisciplinary assessment - Mosquera, Giovanny M. (2023)
Interdisciplinary knowledge is necessary to achieve sustainable management of natural resources. However, research is still often developed in an exclusively disciplinary manner, hampering the capacity to holistically address environmental issues. This study focuses on páramo, a group of high-elevation ecosystems situated around ∼3000 to ∼5000ma.s.l. in the Andes fromwestern Venezuela and northern Colombia through Ecuador down to northern Peru, and in the highlands of Panama and Costa Rica in Central America. Páramo is a social-ecological system that has been inhabited and shaped by human activity since ∼10,000 years BP. This system is highly valued for the water-related ecosystem services provided to millions of people because it forms the headwaters of major rivers in the Andean- Amazon region, including the Amazon River. We present a multidisciplinary assessment of peer-reviewed research on the abiotic (physical and chemical), biotic (ecological and ecophysiological), and social-political aspects and elements of páramo water resources. A total of 147 publications were evaluated through a systematic literature review process. We found that thematically 58, 19, and 23 % of the analyzed studies are related to the abiotic, biotic, and social-political aspects of páramo water resources, respectively. Geographically, most publications were developed in Ecuador (71 % of the synthesized publications). From 2010 onwards, the understanding of hydrological processes including precipitation and fog dynamics, evapotranspiration, soil water transport, and runoff generation improved, particularly for the humid páramo of southern Ecuador. Investigations on the chemical quality of water generated by páramo are rare, providing little empirical support to the widespread belief that páramo environments generate water of high quality.Most ecological studies examined the coupling between páramo terrestrial and aquatic environments, but fewdirectly assessed in-streammetabolic and nutrient cycling processes. Studies focused on the connection between ecophysiological and ecohydrological processes influencing páramo water balance are still scarce and mainly related to the dominant vegetation in the Andean páramo, i.e., tussock grass (pajonal). Social-political studies addressed páramo governance and the implementation and significance ofwater funds and payment for hydrological services. Studies directly addressing water use, access, and governance in páramo communities remain limited. Importantly, we found only a few interdisciplinary studies combining methodologies from at least two disciplines of different nature despite their value in supporting decision-making. We expect this multidisciplinary synthesis to become a milestone to foster interdisciplinary and transdisciplinary dialogue among individuals and entities involved in and committed to the sustainable management of páramo natural resources. Finally, we also highlight key frontiers in páramo water resources research, which in our view need to be addressed in the coming years/decades to achieve this goal.